2013
DOI: 10.1063/1.4801312
|View full text |Cite
|
Sign up to set email alerts
|

Versatile fluoride substrates for Fe-based superconducting thin films

Abstract: We demonstrate the growth of Co-doped BaFe2As2 (Ba-122) thin films on AEF2 (001) (AE: Ca, Sr, Ba) single crystal substrates using pulsed laser deposition. All films are grown epitaxially despite of a large misfit of -10.6% for BaF2 substrate. For all films a reaction layer is formed at the interface confirmed by X-ray diffraction and by transmission electron microscopy. The superconducting transition temperature of the film on CaF2 is around 27 K, whereas the corresponding values of the other films are around … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 29 publications
(31 reference statements)
2
61
3
1
Order By: Relevance
“…The in-plane lattice parameter of Co-doped Ba122 film on CaF 2 is smaller than those of Co-doped Ba122 bulk samples [61,62], which indicates that the film received the in-plane compressive strain. The obtained superconducting transition temperature is T onset c ≈ 28 K [63], which is higher than the highest T c in Co-doped Ba122 bulk samples [61,62].…”
Section: -Systemmentioning
confidence: 94%
See 4 more Smart Citations
“…The in-plane lattice parameter of Co-doped Ba122 film on CaF 2 is smaller than those of Co-doped Ba122 bulk samples [61,62], which indicates that the film received the in-plane compressive strain. The obtained superconducting transition temperature is T onset c ≈ 28 K [63], which is higher than the highest T c in Co-doped Ba122 bulk samples [61,62].…”
Section: -Systemmentioning
confidence: 94%
“…However, in thin films of 1111, 122, and 11, the highest T c is commonly obtained in the case of CaF 2 substrates. Tsukada et al firstly reported the effectiveness of the CaF 2 substrate in the 11 film fabrication [40], and then the fabrication of the film with high T c were reported in other systems [31,41,63]. Here, we define the lattice misfit,…”
Section: Substrate Materials In the Films Fabrication Of Iron-based Smentioning
confidence: 99%
See 3 more Smart Citations